Frugivory on Margaritaria nobilis L.f. (Euphorbiaceae): poor investment and mimetism. - Cazetta, Eliana; Zumstein, Liliane S.; Melo-Junior, Tadeu A.; Galetti, Mauro [UNESP] (My University, 2008)
Dehiscent fruits of Euphorbiaceae usually have two stages of seed dispersal, autochory followed by myrmecochory. Two stages of Margaritaria nobilis seed dispersal were described, the first stage autochoric followed by ornithocoric. Their dehiscent fruits are green and after they detached from the tree crown and fall on the ground, they open and expose blue metallic cocas. We studied the seed dispersal system of Margaritaria nobilis in a semi-deciduous forest in Brazil. In 80 h of focal observations, we recorded only 12 visits of frugivores, however the thrush Turdus leucomelas was the only frugivore that swallowed the fruits on the tree crown. Pitylus fuliginosus (Fringilidae) and Pionus maximiliani (Psittacidae) were mainly pulp eaters, dropping the seeds below the tree. on the forest floor, after fruits dehiscence, jays (Cyanocorax chrysops), guans (Penelope superciliaris), doves (Geotrygon montana) and collared-peccaries (Pecari tajacu) were observed eating the blue diaspores of M. nobilis. Experiments in captivity showed that scaly-headed parrots (Pionus maximiliani), toco toucans (Ramphastos toco), jays (Cyanochorax chrysops), and guans (Penelope superciliaris) consumed the fruits and did not prey on the seeds before consumption. The seeds collected from the feces did not germinate in spite of the high viability. The two stages of seed dispersal in M. nobilis resembles the dispersal strategies of some mimetic species. However M. nobilis seeds are associated with an endocarp, it showed low investment in nutrients, and consistent with this hypothesis, M. nobilis shared important characteristics with mimetic fruits, such as bright color display, long seed dormancy and protection by secondary compounds.

Frutos deiscentes de Euphobiaceae usualmente apresentam dois estágios de dispersão de sementes, sendo autocórico seguido por mirmecocórico. Dois estágios de dispersão de sementes de Margaritaria nobilis foram descritos, sendo o primeiro autocórico seguido por ornitocórico. Os frutos deiscentes desta espécie são verdes e quando caem da copa para o solo, abrem e expõe as cocas azuis metálicas. O sistema de dispersão de sementes de Margaritaria nobilis foi estudado em uma floresta semi-decídua no Brasil. Em 80 horas de observações focais, registram-se apenas 12 visitas de frugívoros, no entanto o sabiá Turdus leucomelas foi o único frugívoro que ingeriu os frutos na copa da árvore. Pitylus fuliginosos (Fringilidae) e Pionus maximiliani (Psittacidae) são principalmente consumidores de polpa, derrubando as sementes abaixo das árvores. No chão da floresta, após a deiscência dos frutos, gralhas (Cyanocorax chrysops), jacus (Penelope superciliaris), pombas (Geotrygon montana) e catetos (Pecari tajacu) foram observados consumindo os frutos azuis de Margaritaria nobilis. Experimentos em cativeiro mostraram que maritacas (Pionus maximiliani), tucanos (Ramphastos toco), gralhas (Cyanochorax chrysops) e jacus (Penelope superciliaris) consumiram os frutos e não predaram as sementes antes do consumo. As sementes coletadas das fezes não germinaram apesar de apresentarem alta viabilidade. Os dois estágios de dispersão de sementes de M. nobilis assemelham-se com a estratégia de dispersão de algumas espécies miméticas. Embora as sementes de M. nobilis estejam associadas com um endocarpo, esses apresentam um baixo investimento em nutrientes e consistente com esta hipótese, M. nobilis compartilha características importantes com outros frutos miméticos, como displays coloridos, longa dormência das sementes e proteção por compostos secundários.
Frugivoria em Margaritaria nobilis L.f. (Euphorbiaceae): pouco investimento em recursos e mimetismo